Do Bulls and Bears Understand Exchange Rate Dynamics? Evidence from Global Scenario - Kulshrestha, Nitin; Aggarwal, Dr. Shalini; Singh, Dr. Navjit (The journal of contemporary issues in business and government, 2021)
The motivation of the present study to investigate and understand the correlation of adjusted closing prices of forex and index (EUR/INR, GDP/INR, Nifty50, CNXIT) which is traded at National Stock Exchange, India. The empirical analysis of three years of data with the help of E-views software. After investigation, it can conclude there is a steady correlation ship among the group. CNXIT having a more robust relationship with Forex as compare to Nifty50. It shows a short-run equilibrium relationship variable but, long-run equilibrium among variables, but shows a very strong co-relation among all the research variable (EUR/INR, GDP/INR, Nifty50, CNXIT. Due to above support it determine the unidirectional price detection dynamics. The co-integration test allows high degree of relationships among variables.